2011
DOI: 10.1203/pdr.0b013e318212f562
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences on Social Cognition

Abstract: Human social behavior develops under the influence of genetic, environmental, and cultural factors. Social cognition comprises our ability to understand and respond appropriately to other people's social approaches or responses. The concept embraces self-knowledge and theory of mind, or the ability to think about emotions and behavior from the perspective of another person. The neuropeptides oxytocin (OT) and vasopressin (AVP) are now known to play an important role, affecting individual differences in parenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 84 publications
(80 reference statements)
2
54
0
Order By: Relevance
“…There is considerable overlap in both region of expression and functional significance of the three neurotransmitter systems described above-oxytocin, dopamine, and serotonin-and interactions between these systems could influence social behavior (Baskerville and Douglas, 2010;Emiliano et al, 2007;Skuse and Gallagher, 2011). In rats, an interaction between oxytocin and dopamine helps regulate maternal behavior (Shahrokh et al, 2010).…”
Section: Other Genetic Pathwaysmentioning
confidence: 99%
“…There is considerable overlap in both region of expression and functional significance of the three neurotransmitter systems described above-oxytocin, dopamine, and serotonin-and interactions between these systems could influence social behavior (Baskerville and Douglas, 2010;Emiliano et al, 2007;Skuse and Gallagher, 2011). In rats, an interaction between oxytocin and dopamine helps regulate maternal behavior (Shahrokh et al, 2010).…”
Section: Other Genetic Pathwaysmentioning
confidence: 99%
“…Moreover, a negative correlation between SER and stress is likely to exist because research has found that touch is associated with increased levels of SER (Field et al, 1996), which have been demonstrated to reduce stress reactivity in humans (Hanley & Van de Kar, 2003). Finally, it is reported that SER desensitizes the AVP receptor (Skuse & Gallagher, 2011), which could reduce approach and trust behavior.…”
Section: Notementioning
confidence: 99%
“…Also OXT shows anxiolytic effects by dampening the amygdala response to social and emotional stimuli (Domes et al 2007a) and therefore acts as a facilitator of prosocial behaviour and interpersonal trust (Baumgartner et al 2008;Heinrichs and Domes 2008;Theodoridou et al 2009; K Ă© ri and Kiss 2011). Moreover, OXT has been shown to interact with the dopaminergic system and thus to stimulate the attribution of salience to social and emotional stimuli and to enable higher social-cognitive functions (Skuse and Gallagher 2009;Rosenfeld et al 2010;Skuse and Gallagher 2011). Dysfunction in this amygdala-dopamino-oxytocinergic circuitry might explain some aspects of the social cognitive defi cits in schizophrenia (Rosenfeld et al 2010).…”
Section: Participantsmentioning
confidence: 99%